Offshore jurisdictions, controversial topic of the modern business world - PĂUN, Roxana-Daniela (Annals of Spiru Haret University. Economic Series, 2010)
This article aims to present synthetically the off-shore jurisdiction issues in the context of the globalisation of our lives and automatically of the business world facing new issues and challenges regarding the business in the international area, starting from defining elements and approaching some of the practical challenges offered by the widespread use of such offshore jurisdictions known as “tax havens”.